Kids in the capitol: improving civic literacy through experiential learning. (3rd July 2017) - Fudge, Daniel; Skipworth, Sue Ann
ABSTRACT: The contemporary education system aides in the development of students' cognitive learning skills to better prepare them for the future; however, education can also prepare students to be more engaged citizens in a democratic society. Civic literacy is a valuable skill for students to learn as it provides a foundation for a better understanding of the complexities of government and the political world. Experiential learning through educational field trips has been proven to stimulate an increased awareness of particular concepts and ideas. In this brief commentary, we demonstrate that civic literacy can be promoted in the minds of young students by exposing them first-hand to the political process. Furthermore, the current understanding of civic literacy is lacking and requires innovative methods to better facilitate learning outcomes that will not only benefit learning outcomes but future civic engagement.